1999
DOI: 10.1111/0162-895x.00150
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Party Identification: A Social Identity Approach

Abstract: Social identity theory holds that individuals derive their self‐concept from knowledge of their membership in a group (or groups) and that they place value and emotional significance on that group membership, with resulting perceptual and attitudinal biases. Individuals favor the in‐group to which they belong which they define against a relevant out‐group. In this study, a partisan social identity scale was used to reinterpret perceptual features of partisanship through the lens of social identity theory. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
248
0
8

Year Published

2000
2000
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 413 publications
(261 citation statements)
references
References 18 publications
5
248
0
8
Order By: Relevance
“…This biased perception results in the development of positive attitude toward one party and negative attitude to all other opposition parties. Greene (1999) further supported the social identity theory and argued that voters have social identifications with political parties that contribute in shaping their perception, attitude and behavior toward political parties.…”
Section: Social Identity As An Outcome Of Political Socializationmentioning
confidence: 80%
See 1 more Smart Citation
“…This biased perception results in the development of positive attitude toward one party and negative attitude to all other opposition parties. Greene (1999) further supported the social identity theory and argued that voters have social identifications with political parties that contribute in shaping their perception, attitude and behavior toward political parties.…”
Section: Social Identity As An Outcome Of Political Socializationmentioning
confidence: 80%
“…Therefore, the members of one group are always in struggle to enhance the in-group difference from the out-groups by exhibiting positive attitude and favoritism toward in-group members (Tajfel and Turner, 1986). The categorization and in-group favoritism leads to the development of biased perception of members belonging to in-group and out-groups (Greene, 1999).This claim was further supported by the study of Kelly (1988) who found that the identification of in-group members and differentiation from out-groups was significantly correlated with each other. Furthermore, she found the positive correlation between biased social identity and self-esteem of the group members.…”
Section: Social Identity As An Outcome Of Political Socializationmentioning
confidence: 99%
“…Status inequality, as explained by social identity theory, is the manifestation of in-group bias (Smith, 1991). Greene (1999) extends this concept to sojourner acceptance within host cultures.…”
Section: Literature Reviewmentioning
confidence: 98%
“…Social Identity Theory (SIT) suggests individuals will be more likely to vote for and support candidates who share similar characteristics with themselves (Conover, 1984;Greene, 1999;Huddy, 2001;Oakes, 2002;Tajfel et al, 1971). The connection with a candidate's identity has been shown to increase the participation rates among women (Bassi, Morton, & Williams, 2011;Dolan, 1998;Matson & Fine, 2006), African Americans (Bobo & Gilliam Jr., 1990), Latinos (Jackson, 2011), and more recently youth (Pomante & Schraufnagel, 2015).…”
Section: Explaining Youth Political Participationmentioning
confidence: 99%